The Effect of Market Capitalization, Trading Volume, Book Value, and Capital Structure on Share Prices - Tanheitafino, Christobal; Helma Malini; Wendy; Giriati; Ramadania, (International Journal of Scientific Research and Management (IJSRM), 2023)
The share price represents the company's value on the share market; buyers and sellers establish the company's value based on the quantity of demand and supply of shares. This research looks at how market capitalization, trading volume, BV, and DER are used to analyze share price variations. The research aims to understand investor behavior in fluctuating market situations. The method used is to analyze multiple linear regression, and the data collection method is secondary data. This study's results indicate a relatively significant correlation between market capitalization, trading volume, BV, DER, and share prices, implying that predictor variables may adequately describe the reasons for price fluctuations. The conclusion of the research results reveals that from 2019 to 2021, investors act rationally in making judgments while conducting transactions or preserving their cash in the Bank and Insurance Sub-Sector.JEL, classification：G11 G12Keywords: Market Capitalization; Trading Volume; BV; DER; Share Stocks